1975
DOI: 10.1161/01.str.6.5.535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclandelate on Dementia

Abstract: Abstract:Effect of Cyclandelate on Dementia• Cyclandelate, a vasodilator, was administered to 24 patients with dementia. The dementia in these patients was presumed to be due to cerebral ischemia caused by atherosclerosis in cerebral vessels after other possible causes were ruled out. In a double-blind, cross-over study, patients received 200 mg of cyclandelate four times daily for six weeks and a placebo for six weeks. Six psychological tests, which reflect various aspects of higher cortical ability, were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The clinical efficacy, unfortunately, has not been documented so clearly. Although several investigators have reported positive results (6–9), others have reported equivocal (10) or negative results (11). Nevertheless, it is apparent that in the past vasodilators have too often been prescribed indiscriminately, without proper selection of patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical efficacy, unfortunately, has not been documented so clearly. Although several investigators have reported positive results (6–9), others have reported equivocal (10) or negative results (11). Nevertheless, it is apparent that in the past vasodilators have too often been prescribed indiscriminately, without proper selection of patients.…”
mentioning
confidence: 99%
“…The positive effect of cyclandelate on the attributes of impairment of recent memory, mood depression, irritability, hostility, indifference to surroundings and anxiety was significantly superior to that of placebo as early as the eighth week of treatment ( Table 2). (6)(7)(8)(9), others have reported equivocal (10) or negative results (11). Nevertheless, it is apparent that in the past vasodilators have too often been prescribed indiscriminately, without proper selection of patients.…”
mentioning
confidence: 99%
“…Vinpocetine may also function as a cerebral vasodilator. We would not expect a vasodilator to be effective in AD, because other cerebral vasodilators have been ineffective in this disorder 22, 23 …”
Section: Discussionmentioning
confidence: 99%
“…One such drug, cyclandelate (Cyclospasmol, Ives Laboratories Inc), has a clearly demonstrated effect on the cerebral circulation (1–3). However, clinicians have had difficulty in relating these physiologic effects with clinical improvement, and the results of several clinical studies have varied from strongly positive (4–6) to equivocal (7) or even negative (8).…”
mentioning
confidence: 99%